2018
DOI: 10.11152/mu-1633
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic features of superficial and nodular basal cell carcinoma

Abstract: Aim: To describe the ultrasonographic findings of surface and nodular basal cell skin cancer (BCC) using high frequency ultrasonography.Materials and methods: We examined 60 primary BCCs in different locations with the High Frequency Ultrasound (HFU) system DUB Skin Scanner using 75 MHz and 30 MHz probes. Epidermis, dermis, and depth of tumors spread in the region of interest (ROI) were measured. Visually unchanged, contralateral skin areas were examined as the control. Results: The surface BCC most often had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…It depends on the lesion size, including the invasion depth, anatomical location, and clinical type of the tumor [9][10][11]. These parameters can be successfully assessed with HFUS skin imaging [6,[12][13][14].…”
Section: The Use Of Hfus In Dermato-oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…It depends on the lesion size, including the invasion depth, anatomical location, and clinical type of the tumor [9][10][11]. These parameters can be successfully assessed with HFUS skin imaging [6,[12][13][14].…”
Section: The Use Of Hfus In Dermato-oncologymentioning
confidence: 99%
“…The presence and count of hyperechoic spots in BCC are considered as risks for a local BCC recurrence. Ultrasonographic features of superficial and nodular basal cell carcinoma were also analyzed and described [12][13][14]20]. Below, there are examples of various BCC sub-types assessed by HFUS (Figures 7, 8).…”
Section: The Use Of Hfus In Dermato-oncologymentioning
confidence: 99%
“…Wortsman et al [15] summarized that US examination of BCC tumours may evaluate characteristic hyperechoic spots which can confirm the diagnosis and also help in the prediction of high recurrence risk histologic subtypes. Other studies including NMSC concluded that hyperechoic spots can be visualised on grayscale US and can differentiate BCC from other tumours [28,32,35,36].…”
Section: Relevant Data From the Recent Literaturementioning
confidence: 99%
“…In earlier studies, the use of a 20 MHz frequency probe allowed to detect BCC as a hypoechoic zone with local thickening of the epidermis and the dermis (21) . All clinical variants of BCCs were defined as a hypoechoic zone located directly beneath the epidermis and propagating into the dermis at a varying depth, mostly round or oval (22) . Similar HFUS images were obtained in our study using a 48 MHz probe.…”
Section: Basal Cell Carcinoma (Bcc)mentioning
confidence: 99%